Let's change the world how to work within international development organizations to make a difference - Vegas, Emiliana (Lanham Rowman & Littlefield, 2024)
"An informative guide to building and navigating a career in international development for current and aspiring changemakers"-- Provided by publisher.
Includes bibliographical references (page 201) and index.
Keywords: Economic assistance; International agencies; Non-governmental organizations